Wikipedia in academic community: perceptions and experiences of students and teachers (Libellarium: journal for research in the field of information and related sciences, 2016)
The paper presents results of the study into perceptions and experiences of students and teachers in relation to the use of online encyclopaedia Wikipedia for academic purposes. In the study authors tried to answer the following research questions: “How do students and teachers perceive Wikipedia, as a source of academic information?”, “Are there any differences between students and teachers?”, “Do teachers consult Wikipedia in their academic work?”, “Why and how do students use Wikipedia for academic purposes?”, and “What factors influence students’ and teachers’ perceptions and uses of Wikipedia?”. The study was conducted among students and teachers at Osijek University, Croatia, with the help of online and print survey. In respect to the perception of Wikipedia, the study showed that students had a more positive opinion of Wikipedia than teachers, and that among students there are differences in respect to their gender, scientific area and the frequency of their use of academic libraries and online databases. In relation to teachers, the statistically significant difference was found only in respect to the gender of respondents: male teachers had in general more positive attitude toward Wikipedia than their female colleagues. Although results show that teachers themselves rarely use Wikipedia for academic purposes, only 19.8% of respondents explicitly forbid their students to use this source. While teachers use Wikipedia more frequently in teaching than in the context of research and scientific work, students use Wikipedia to a larger degree because it is easily searchable than because it offers quality and reliable information. While for teachers’ use of Wikipedia no statistically significant differences were found (e.g. gender, scientific area), in examining students’ use of Wikipedia significant differences were found in relation to gender, level of study, scientific area, academic success, frequency of the academic library use and the perceived attitude of their teachers toward Wikipedia. Despite limited sample and drawbacks inherent to the method and instrument used, the results of the study can contribute to the understanding of students and teachers’ information behavior in academic context, and in particular in relation to the online encyclopaedia Wikipedia. At the same time, the results of this study can be used by academic teachers and librarians when preparing their classes in information literacy and evaluation of online sources in particular.
Keywords: students; Wikipedia; teachers; perceptions; experiences; study; Croatia